The Aspect of Gender Identity in the Gothic Novel Genre and the Identity of Women Characters in Selected Works of Fiction by Milos Urban - Antos, Matej (Bohemica Olomucensia, 2016)
The gothic novel is often assumed as one of the first genre where the writing women assert themselves. Therefore, the paper's first part is focused on this episode of the history of literature and establishing of the distinctive sub-genre of the female gothic. This new mode of writing not only helped women to begin to cope with their position within the society, it also created a narrow but gradually enlarging path to the world literature for the writing women. The second part of the study focuses on female characters in selected works of fiction by Milos Urban. From the analysis and its conclusion results is noticeable that however the main characters of Urban's novels are men and the female characters often act within stereotypic gender roles, a few sporadic exceptions can be nevertheless found and pointed out.
Keywords: gothic novel; gothic fiction; female writing; female gothic; gender studies; feminist literary criticism; Milos Urban; Czech literature